2020
DOI: 10.1186/s12864-020-06949-5
|View full text |Cite
|
Sign up to set email alerts
|

Relatively semi-conservative replication and a folded slippage model for short tandem repeats

Abstract: Background The ubiquitous presence of short tandem repeats (STRs) in virtually all genomes implicates their functional relevance, while a widely-accepted definition of STR is yet to be established. Previous studies majorly focus on relatively longer STRs, while shorter repeats were generally excluded. Herein, we have adopted a more generous criteria to define shorter repeats, which has led to the definition of a much larger number of STRs that lack prior analysis. Using this definition, we analyze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The first construction of the locus maps of HDMA peaks clearly revealed that these HDMA peaks are distributed regularly along every human chromosome in both the reference (GRCh38) and first complete (CHM13) human genome, suggesting that the high-density microsatellites accumulation is probably the necessary fundamental elements in human genome. We formerly presented a folded slippage model for repeats occurring mechanism, predicting that micro-disturbing in the process of replication may provide a lot of chances for the template chain folded to produce repeats, which are possibly selected fixation for different biological significance in the long-history evolution [44]. Among all motif types of HDMA peaks, more than half of HDMA peaks are AT n motif type in the GRC38 and CHM13 human genome, suggesting that AT n motif is the most specific STRs motif among all STRs motifs and tend to accumulate in human genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first construction of the locus maps of HDMA peaks clearly revealed that these HDMA peaks are distributed regularly along every human chromosome in both the reference (GRCh38) and first complete (CHM13) human genome, suggesting that the high-density microsatellites accumulation is probably the necessary fundamental elements in human genome. We formerly presented a folded slippage model for repeats occurring mechanism, predicting that micro-disturbing in the process of replication may provide a lot of chances for the template chain folded to produce repeats, which are possibly selected fixation for different biological significance in the long-history evolution [44]. Among all motif types of HDMA peaks, more than half of HDMA peaks are AT n motif type in the GRC38 and CHM13 human genome, suggesting that AT n motif is the most specific STRs motif among all STRs motifs and tend to accumulate in human genome.…”
Section: Discussionmentioning
confidence: 99%
“…Among all motif types of HDMA peaks, more than half of HDMA peaks are AT n motif type in the GRC38 and CHM13 human genome, suggesting that AT n motif is the most specific STRs motif among all STRs motifs and tend to accumulate in human genome. The folded slippage replication possibly explain why short and A/T repeat-motifs occur much more frequently than long and C/G repeat-motifs [44], however, there is no A n and T n motif accumulation peak but many AT n motif accumulation peaks (Fig 2C -2E, Table S6), further indicating that AT n motifs might have been specifically selected as very essential elements for genome structures and functions to fix and accumulate in these chromosomes. And the comparison of HDMA peaks between the GRCh38 and CHM13 human genomes clarified that the sequence of HDMA peaks are higher variable with exhibiting repeat motifs expanding or contacting dramatically, this is consistent with many former observation that STRs are liable to mutation through repeat units expanding or contacting [45][46][47], indicating that the variation of HDMA peaks probably affect regulatory and then related to variation of gene expression profiles, and further may act to human phenotypes and human variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological sequences are complex and full of subtle patterns; however, one of the most common patterns is not subtle at all: tandem repeats. Tandem repeats are a class of biological sequences that, for various reasons [1][2][3][4], consist of multiple adjacent copies of some core repetitive unit. "AACAACAACAACAACAACAACAAC" is an example of a short tandem repeat composed of an "AAC" unit repeated 8 times.…”
Section: Tandem Repeatsmentioning
confidence: 99%
“…An assortment of repeat expansion mechanisms is responsible for the various classes of tandem repeats. Short tandem repeats [ 5 ] are primarily caused by replication slippage [ 1 , 6 ] and have small repetitive units from 1 to 6 bp, which can repeat to span up to hundreds of bp [ 7 , 8 ]. Minisatellites [ 9 ] are a larger sort of tandem repeat, having units between 6–60 bp and occupying regions as large as 20 kb [ 10 ].…”
Section: Introductionmentioning
confidence: 99%